Digital elevation model and satellite gravity anomalies and its correlation with geologic structures at Borena basin, in the Southern Main Ethiopian Rift. Issue 1 (31st December 2022) - Abdulkadir, Yahya Ali; Fisseha, Shimeles; Jothimani, Muralitharan
ABSTRACT: This study integrates remote sensing data via Digital Elevation Model (DEM) and satellite gravity data to detect geologic structurs at Borena and the surrounding regions in the Southern Main Ethiopia Rift (SMER). Shading from different sun azimuths with 45-degree intervals and the tilt angle method was used to map lineaments and detect edges of anomalies from the DEM and gravity data, respectively. The area's geology comprises quaternary alluvial and eluvial sediments, pre-rift and rift volcanic rock, and Precambrian banded gneiss. The Ririba, Mega and Chew Bahir rift systems make the main structural fabric of the area. About 793 lineaments from DEM data and 441 from gravity data were outlined, and their orientations were analyzed using rose diagrams. These are trending dominantly in NW to SE and N to S directions. From the gravity data analysis, the depth of anomalies ranges from 300 m to more than 7 km below the ground, with most of the lineaments being at shallow depth. The results obtained agree with the main tectonic features found in the study area. The integration of remote sensing data has facilitated delineating structural features in studying the regional geology of the large area.